Comparative Modeling and Molecular Docking of Alcohol Acyltransferase in Fruit Aroma Biosynthesis - Kamillah, Wa Ode; Siti Purnamasari, Wa Ode (Jurnal Biologi Tropis, 2025)
Fruit aroma arises from volatile esters synthesized by alcohol acyltransferase (AAT) of the BAHD family. This study analyzes AATs from Citrus sinensis, Vitis vinifera, Malus domestica, and Fragaria × ananassa through sequence alignment, secondary structure prediction, 3D modeling, and docking with acetyl-CoA. Secondary structure prediction shows conserved α-helices and β-sheets forming the characteristic α/β fold, with loops providing interspecies variation. all AATs retain the HXXXD motif and DFGWG/NFGWG variants with ~450 residues. Docking reveals a consistent acetyl-CoA orientation but species-specific interactions: polar/charged residues (Arg, Ser, His, Gln/Asn) form hydrogen and electrostatic bonds, whereas aromatic/aliphatic residues (Phe, Ile, Met) provide hydrophobic stabilization. Malus domestica exhibits the strongest polar network (6 H-bonds; ≈ −7.8 kcal·mol⁻¹), whereas Citrus sinensis relies more on hydrophobic contacts (≈ −6.9 kcal·mol⁻¹). These findings indicate that a conserved structural framework preserves the core catalytic mechanism of AATs while species-specific active-site microarchitecture modulates substrate affinity and selectivity, likely contributing to differences in fruit volatile ester profiles and offering candidate residues for targeted functional validation and aroma improvement.